Food-related stories - Melian, Gaby (Pocket change collective., 2021)
"Chef and activist Gaby Melian shares her personal journey with food--from growing up in Argentina to her time as a street vendor and later as Bon Appetit's test kitchen manager. Melian explores how we can develop a relationship with food that's personal, healthy, and thoughtful"--